Optimality of the Disclosure of Private Information in a Production‐Exchange Economy - TRUEMAN, BRETT (Journal of Finance, 1983)
ABSTRACT This study provides an analysis of the effects on individual welfare of information revelation in a production‐exchange economy. It is shown that the total effect of information revelation on an agent's utility level may be decomposed into three elements: a price effect, a shareholding effect, and a production effect. Through this decomposition, it is demonstrated that, although a Pareto improvement need not result from information revelation, there are perspectives from which the release can be considered beneficial.